P071 NO INCREASED RATE OF ADVERSE IBD-RELATED OUTCOMES FOR PATIENTS WITH IBD AND CONCURRENT PROSTATE CANCER TREATED WITH RADIATION THERAPY. (7th February 2019) - Feagins, Linda A; Kim, Jaehyun; Chandrakumaran, Anchalia; Gandle, Cassandra; Naik, Katrina; Hou, Jason K; Yao, Michael; Gaidos, Jill
Abstract: Background: Some physicians have concern that radiation treatment for prostate cancer may precipitate flares or complications in patients with inflammatory bowel disease (IBD). However, controversy remains due to limited data in regard to the best treatment approach for patients with IBD who develop prostate cancer. Aims: To compare IBD-related outcomes for patients with concomitant IBD and prostate cancer depending on the treatment modality received for their prostate cancer. Methods: We performed a retrospective cohort study across 4 VA hospital systems (Dallas, TX; Houston, TX; Washington DC; Richmond, VA). Patients with established IBD who were diagnosed and treated for prostate cancer between 1996 – 2015 were included. We assessed for 1) flares of IBD, IBD-related hospitalizations, and IBD-related surgeries within 6, 12 and 24 months of cancer diagnosis and 2) survival at 1, 2 and 5 years post-cancer diagnosis. Results: 94 patients with IBD (31% Crohn's, 64% UC, 5% Indeterminate colitis) were identified who were diagnosed with prostate cancer and underwent treatment. Of these 94 patients, 45 were treated with either XRT (76%) or brachytherapy (24%) and 49 were treated with other non-radiation modalities of prostate cancer therapy (82% surgery, 13% hormonal, 2% chemotherapy). Comparing patients treated with or without radiation, there were no differences in disease type (UC versus CD), race, age at diagnosis of IBD or cancer, Charlson comorbidity index, Gleason scores, pre-treatment PSAs, T-stage, or D'Amico score (table 1). There were no differences in rates of IBD flares, IBD hospitalizations, or IBD surgeries at 6, 12, or 24 months after cancer diagnosis for those treated with radiation versus other treatment modalities (table 2). There were no differences in survival at 1, 2 or 5 years after cancer diagnosis for patients treated with radiation versus those treated with other modalities. Conclusion: In this retrospective, multicenter study, no difference in IBD-related outcomes or survival was found between patients with IBD treated with or without radiation for their prostate cancer. These data support the notion that radiation therapy need not be avoided for patients with IBD.